Review Article: Buddhist Sūtras in Sanskrit from the Potala - Silk, Jonathan A. (Indo-Iranian journal, 2013)
The recent publication of twenty shorter Buddhist sūtras in Sanskrit edited from a manuscript kept in the Potala Palace, with corresponding editions of Tibetan and Chinese translations, when available, is a noteworthy contribution to our inventory of Indian scriptural materials. The present contribution offers several suggestions for improvement to the edited texts in anticipation of their further future study.